Development of Healthy Ready-to-Cook Sauce for Thai Food - Vittayaporn, Varaporn; Onnompun, Ekapon; Wirunthanakrit, Weerapong (Journal of Food Health and Bioenvironmental Science, 2023)
Being widely popular both internal and external to Thailand in the meantime, Thai cuisine is characterised by the use of herbs and spices as a part of the ingredients to provide their unique flavors. However, due to the vast variety in its ingredients and the delicacy in preparing or even the difficulty in acquiring the ingredients indicated in the formula, the flavors of the dish are very likely to be distorted from authenticity. This research therefore aims to develop ready-to-cook sauces for Thai food to increase convenience for consumers and to survey consumers’ acceptance of these products. Additionally, tea seed oil and powdered Gac are also utilised for their health-wise beneficial values. The developed ready-to-cook sauces include Pad Thai sauce and Ka Phrao (Holy basil) sauce. The result of product acceptance test indicated that consumers rated the liking scores for Pad Thai sauce and Ka Phrao sauce in the range between like moderately and like very much (8.2±1.3 and 7.8±1.2). Over 92% of the consumers accepted the both sauce products, and more than 89 % decided to purchase the products. Hence, the development of the healthy ready-to-cook sauce products is viable for commercial distribution.